2019
DOI: 10.1080/17437199.2019.1650290
|View full text |Cite
|
Sign up to set email alerts
|

Trait mindfulness and health behaviours: a meta-analysis

Abstract: Mindfulness is defined as bringing one's attention to present-moment experience with acceptance, and is associated with engagement in various health behaviours. To synthesise and evaluate this literature, we conducted a comprehensive meta-analytic review and examined (a) the associations between trait mindfulness and health behaviours and (b) the extent to which these associations were moderated by study and individual differences. A total of 125 independent samples were included (N = 31,697, median male perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 185 publications
7
83
1
5
Order By: Relevance
“…These combinations are perceived stress and self‐care agency, depressive symptoms and self‐care agency, and perceived stress with depressive symptoms and self‐care agency. The importance of these results lies in supporting the argument that the association between mindfulness and health promotion is rather complex (Sala et al., 2019). In addition, they provide insights regarding conducting future research with a central recommendation that researchers should consider serial multiple mediation in favour of parallel multiple mediation.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These combinations are perceived stress and self‐care agency, depressive symptoms and self‐care agency, and perceived stress with depressive symptoms and self‐care agency. The importance of these results lies in supporting the argument that the association between mindfulness and health promotion is rather complex (Sala et al., 2019). In addition, they provide insights regarding conducting future research with a central recommendation that researchers should consider serial multiple mediation in favour of parallel multiple mediation.…”
Section: Discussionmentioning
confidence: 54%
“…Studying issues pertinent to health promotion could have a positive impact on college students’ life in the near future through improving academic success (Leland, 2015) and overall well‐being (Van der Riet et al., 2018; White, 2013). Preventing or reducing the risk of chronic diseases later in life could also be an outcome of supporting health promotion during college life (Sala et al., 2019). The results of the current study showed that mediators demonstrate a key role in determining the relationship between mindfulness and health promotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Shaw et al, 2019 Environmental interventions such as health promotion education and labelling improve dietary behaviours. (Sala et al, 2019) Mindfulness (bringing one's attention to present moment) is associated with eating health behaviours (rs=0.14, 95% CI: 0.08-0.19).…”
Section: Referencementioning
confidence: 99%
“…Mindfulness is an inherent psychological characteristic trait typified by an ability to be lucidly aware of present moment experience, an open, accepting, and curious engagement with present moment experience, and a non-judgemental, accepting, and self-compassionate attitude to oneself [29]. Naturally occurring 'trait' mindfulness is positively related to higher physical activity and healthy eating, lower alcohol consumption, higher positive affect and wellbeing, and lower perceived stress, antenatal depression, pregnancy-related distress, and general anxiety in pregnancy [27,30].…”
Section: Introductionmentioning
confidence: 99%